2006
DOI: 10.1002/app.22612
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a persimmon leaves (PL)/poly(acrylonitrile) (PAN) blend bio‐fiber

Abstract: Adopting persimmon leaves, PL, as a biomaterial to blend with poly(acrylonitrile) (PAN) via the wet spinning method, a PL/PAN blend biofiber was fabricated. On the basis of mechanical measurements, X-ray diffraction, and DSC characterization, it was found that this biofiber has acceptable mechanical properties for further applying to different cases. Results also showed that though the crystal structure, especially the crystal size, is changed indeed for blend fiber, it seems to be of less influence on the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…These thermal behaviors suggested that the interactions occurred between the polyphenols, and the cyan groups of PAN decreased with increasing TP percentage because the crystal area decreased in the formed interpenetration network. This was possible and was supported by the literature, as a similar thermal phenomenon was also found for some PAN/biomaterial blends …”
Section: Resultssupporting
confidence: 85%
“…These thermal behaviors suggested that the interactions occurred between the polyphenols, and the cyan groups of PAN decreased with increasing TP percentage because the crystal area decreased in the formed interpenetration network. This was possible and was supported by the literature, as a similar thermal phenomenon was also found for some PAN/biomaterial blends …”
Section: Resultssupporting
confidence: 85%
“…At 2u ¼ 16.68 (100 peak) and 2u ¼ 29.88 (110 peak) there exist obvious diffraction peaks; between them there is a board scattering region which indicates that a large fraction is amorphous. [11] The addition of the PDA could contribute to the amorphous scattering, PDA likely being amorphous due to the large numbers of side chains.…”
Section: Analysis Of the X-ray Diffractionmentioning
confidence: 99%